IMPLANTATION D'UN SERVICE DE L'I.S.T. A L'IREQ/(ESTABLISHING A S.T.I. SERVICE AT THE IREQ) - Djoric, Nicolas (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF